2018
DOI: 10.1186/s12891-018-2244-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of arthroscopic rotator cuff repair: a retrospective comparison of double-layer, double-row and suture bridge methods

Abstract: BackgroundThe suture-bridge (SB) method has recently become the mainstream means of repairing full-thickness rotator cuff tears. However, in some patients the deep and superficial layers have moved in different directions because of delamination of their rotator cuffs. In such cases, a simple suture (double-layer, double-row [DD] method) is used to repair the superficial and deep layers separately. The purpose of this study was to analyze the clinical outcomes and re-tear rates of the DD and SB methods, with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…In general, rotator cuff repair techniques are divided into singlerow and double-row repair techniques. It has been reported that there was no statistical difference in retear rate between the two techniques [14]; however, long-term follow-ups and systematic review studies have shown that the retear rate after single-row repair was signi cantly higher than that after double-row repair [8,17].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In general, rotator cuff repair techniques are divided into singlerow and double-row repair techniques. It has been reported that there was no statistical difference in retear rate between the two techniques [14]; however, long-term follow-ups and systematic review studies have shown that the retear rate after single-row repair was signi cantly higher than that after double-row repair [8,17].…”
Section: Discussionmentioning
confidence: 97%
“…In general, rotator cuff repair techniques are divided into single-row and double-row repair techniques. It has been reported that there was no statistical difference in retear rate between the two techniques [14];…”
Section: Introductionmentioning
confidence: 90%
“…In the study in which Burks et al [41] evaluated the results of medium-sized rotator cuff tears, they detected a retear rate of 10% in both groups at the end of 1 year after single- or double-row repairs. In another recent retrospective study, Kakoi et al [42] couldn't detect any difference between the retear rates of single- and double-row constructs at average 16 months follow-up.…”
Section: Introductionmentioning
confidence: 96%
“…The standard treatment for RC tears is surgical reattachment of the torn tendon on to its anatomical insertion. This treatment is reported to result in approximately 50% improvement in shoulder function in 1.5 years [ 5 ]. Although recovery of shoulder function after conservative treatment has been reported to be comparable with surgical repair [ 6 ], healing of the injured tendons was less favourable.…”
Section: Introductionmentioning
confidence: 99%